48a3bc2 ÷ 3abc

Question

Asked 12/6/2010 9:03:55 AM

Updated 3/9/2014 12:47:00 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [3/9/2014 12:47:00 PM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Expert answered|craig1990|Points 65|

Question

Asked 12/6/2010 9:03:55 AM

Updated 3/9/2014 12:47:00 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [3/9/2014 12:47:00 PM]

Rating

8

(48a^3bc^2) ÷ (3abc)

= 16a^2c

= 16a^2c

Added 3/9/2014 12:46:59 PM

This answer has been confirmed as correct and helpful.

y9 ÷ y3 **Weegy:** = y3 **User:** -mnp(3m - 5n + 7p) **Weegy:** why don't you do homeworks? you think you will cheat all your life? (More)

Question

Expert Answered

Updated 3/9/2014 12:51:08 PM

2 Answers/Comments

y9 ÷ y3

= y^6

= y^6

Added 3/9/2014 12:50:03 PM

This answer has been confirmed as correct and helpful.

-mnp(3m - 5n + 7p)

= -3m^2np + 5mn^2p - 7mnp^2

= -3m^2np + 5mn^2p - 7mnp^2

Added 3/9/2014 12:51:08 PM

This answer has been confirmed as correct and helpful.

-mnp(3m - 5n + 7p) **Weegy:** why don't you do homeworks? you think you will cheat all your life? **User:** (6a + b)^2 **Weegy:** The equation is not complete. Can you provide me with the whole equation so that I can give you a solution? (More)

Question

Expert Answered

Updated 3/9/2014 12:52:40 PM

2 Answers/Comments

-mnp(3m - 5n + 7p)

= -3m^2np + 5mn^2p - 7mnp^2

= -3m^2np + 5mn^2p - 7mnp^2

Added 3/9/2014 12:51:47 PM

This answer has been confirmed as correct and helpful.

(6a + b)^2

(6a + b)(6a + b)

36a^2 + 6ab + 6ab + b^2

= 36a^2 + 12ab + b^2

(6a + b)(6a + b)

36a^2 + 6ab + 6ab + b^2

= 36a^2 + 12ab + b^2

Added 3/9/2014 12:52:40 PM

This answer has been confirmed as correct and helpful.

(6a + b)2 **Weegy:** 12z + 2b **User:** Simplify 5 + 2{x - 4[3x + 7(2 - x)]}. **Weegy:** (3x-2) squared is 9x^2 - 12x + 4. **User:** 5 + 2{x - 4[3x + 7(2 - x)]}. **Weegy:** x = 3 **User:** (y3 - 125) ÷ (y - 5) **Weegy:** y = 31 (More)

Question

Expert Answered

Updated 9/28/2014 7:39:35 PM

7 Answers/Comments

(6a + b)^2

= (6a+b)(6a+b)

= 36a^3 + 12ab + b^2

= (6a+b)(6a+b)

= 36a^3 + 12ab + b^2

Added 9/26/2014 11:25:16 PM

This answer has been flagged as incorrect.

Flagged by yeswey [9/28/2014 7:39:11 PM]

5 + 2{x - 4[3x + 7(2 - x)]}

= 5 + 2x + 32x - 112

= (2x + 32x) + (5 + - 112)

= 34 + - 107

= 5 + 2x + 32x - 112

= (2x + 32x) + (5 + - 112)

= 34 + - 107

Added 9/26/2014 11:26:25 PM

This answer has been flagged as incorrect.

Flagged by yeswey [9/28/2014 7:34:26 PM]

5 + 2{x - 4[3x + 7(2 - x)]}

= 5 + 2[x - 4(3x + 14 - 7x)]

= 5 + 2[x - 4(14 - 4x)]

= 5 + 2(x - 56 + 16x)

= 5 + 2(17x - 56)

= 5 + 34x - 112

= 34x - 107

= 5 + 2[x - 4(3x + 14 - 7x)]

= 5 + 2[x - 4(14 - 4x)]

= 5 + 2(x - 56 + 16x)

= 5 + 2(17x - 56)

= 5 + 34x - 112

= 34x - 107

Added 9/28/2014 7:34:18 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/28/2014 11:11:47 PM]

(y^3 - 125) ÷ (y - 5)

=(y^3 - 5^3)/(y - 5)

= (y - 5)(y^2 + 5y + 25)/(y - 5)

= y^2 + 5y + 25

=(y^3 - 5^3)/(y - 5)

= (y - 5)(y^2 + 5y + 25)/(y - 5)

= y^2 + 5y + 25

Added 9/28/2014 7:37:38 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/28/2014 11:12:04 PM]

(2p + 7)(3p - 9) **Weegy:** 6pp + 21p + 18 - 35 (More)

Question

Expert Answered

Updated 3/9/2014 12:48:15 PM

1 Answer/Comment

(2p + 7)(3p - 9)

6p^2 + 21p - 18p - 63

= 6p^2 + 3p - 63

6p^2 + 21p - 18p - 63

= 6p^2 + 3p - 63

Added 3/9/2014 12:48:15 PM

This answer has been confirmed as correct and helpful.

38,691,448

questions answered

There are no comments.